Tandem mass tag-based proteomic profiling revealed potential therapeutic targets and mechanisms of liraglutide for the treatment of impaired glucose tolerance - Guo, Qiuyue; Han, Cong; Xu, Yunsheng; Chen, Qingguang; Han, Xu; Zhao, Sen; Li, Jie; Lu, Hao (Frontiers in Endocrinology, 2022)
Objective: Based on the tandem mass tag (TMT) technique, this study investigated the potential therapeutic targets of Liraglutide (LIRA) on streptozotocin (STZ) -induced Impaired glucose tolerance (IGT) in rats and discussed the biological mechanism of the drug against IGT. Methods: 10 rats were randomly selected from 31 male Wistar rats of SPF grade as Control and fed with conventional chow. The remaining rats were given a high-sugar and high-fat diet combined with an intraperitoneal injection of STZ to establish the IGT model, and 2 non-model rats were excluded. Model rats were randomly divided into Model group (n=10) and LIRA group (n=9). The LIRA group was subcutaneously injected with 0.06 mg/kg LIRA, and metabolic parameters such as body weight and fasting blood glucose were recorded during the period. After 8 weeks, samples were taken under anesthesia. HE staining was used to observe the cell morphology, immunofluorescence was performed on the pancreatic tissues of the three groups of rats, TMT proteomic labeling method was used to determine the expression of differential proteins in pancreatic tissues of the three groups of rats, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) biological function analysis were performed on the intersection of Model and LIRA differential proteins. Results: LIRA could significantly reduce blood glucose levels and improve islet cell morphology and function in IGT rats. Among the differential proteins between the model group and the blank group, 44 were reversed after LIRA treatment, of which 14 were up-regulated and 30 were down-regulated, including PPIF, MPRIP, CYP51, TXNL1, BCL-2, etc. (FC＞1.1 or＜0.909, P＜0.05). GO and KEGG analysis showed that it was related to biological processes such as fatty acid metabolism and adipocyte generation, involving multiple signaling pathways that regulate the function of islet cells, such as MAPK, PI, Ras, FcγR and unsaturated fatty acids, and pyruvate metabolism. Conclusion: LIRA participated in anti-IGT therapy by regulating multiple target proteins and multiple biological functions. This study provided a basis and direction for further exploring the mechanism of action of LIRA at the protein level of IGT.